Peran Sistem Informasi Manajemen Dakwah dalam Transformasi Dakwah Islam di Era Digital - Hilda Rahmadani Harahap; Dewi Silvia Haloho; Thio Andriarta; Alfisyahrin Daulay; Mawaddah Panjaitan; Nazua Azura (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The rapid development of technology has transformed various aspects of human life, including the way religious teachings are conveyed. Da’wah activities, which were traditionally conducted through direct meetings, regular study gatherings, and religious assemblies, have now evolved into the dissemination of religious messages through digital media. This shift is made possible by advancements in internet technology, various communication applications, and other online platforms. Such changes demand structured information management to ensure that da’wah processes remain organized, effective, and aligned with modern progress.This paper aims to examine the role of management information systems in supporting the transformation of Islamic da’wah within the technological era. The study employs a literature review method, analyzing relevant scientific references, books, and previous publications. The results indicate that the system assists in planning, organizing, implementing, and evaluating technology-based da’wah activities. Moreover, adopting digital tools broadens outreach, enhances communication quality, and allows the public to access religious materials conveniently anytime and anywhere.Despite these positive impacts, this transformation faces challenges such as low technological literacy, data security risks, misinformation, and limited human resources skilled in technology. Therefore, developing more sophisticated information systems and improving digital competence among da’wah managers are essential to ensure Islamic propagation runs optimally and remains relevant to current developments.